Assessment of Interleukin (IL-10) Level in the Serum, Placenta and Amniotic Fluid of Aborted Women Infected with HCMV - Siham J. Mohsin (Journal of Global Pharma Technology, 2018)
This research was conducted on 48 women who suffered from spontaneous abortion for one and multiple fold during the first and second stage of pregnancy and with age averages ranging from 14-43 years. which have been confirmed to be infected with the Human Cytomegalovirus (HCMV) by using the Enzyme Link Fluorescent Assay technique (ELFA) ,However, they did not suffer from chronic diseases such as blood pressure, diabetes and other immune diseases , In order to measure the level of interleukin (IL-10) by the enzyme-linked immunosorbent assay (ELISA) in blood samples, placenta and amniotic fluid that collected from women at the time of abortion and while they were in the Curettage Hall of Al -Zahra Hospital and Al-Hakim Teaching Hospital / Najaf Governorate, For the period from October 2015 to April 2016, comparison was made with 10 women who had no history of previous miscarriage or inflammatory disease and had been as control group. The results showed no significant differences between the level of the inflammatory inhibition factor interleukin (IL-10), that measured in the serum of abortive women and the control group, which reaching the level to (5.905 ± 1.5707) Pg/ml. also noted high Significant decrease P ≤ (0.01) in the interleukin (IL-10) concentration that measured in the placenta and amniotic fluid of abortive women compared to healthy Control group. From the above results, concluded that the decrease level of interleukin (IL-10) in abortive women infected with virus may be plays a major role in cases of spontaneous abortion.Keywords: HCMV, Abortion, interleukin (IL-10), ELISA.